2011
DOI: 10.1371/journal.pone.0025339
|View full text |Cite
|
Sign up to set email alerts
|

Stability versus Neuronal Specialization for STDP: Long-Tail Weight Distributions Solve the Dilemma

Abstract: Spike-timing-dependent plasticity (STDP) modifies the weight (or strength) of synaptic connections between neurons and is considered to be crucial for generating network structure. It has been observed in physiology that, in addition to spike timing, the weight update also depends on the current value of the weight. The functional implications of this feature are still largely unclear. Additive STDP gives rise to strong competition among synapses, but due to the absence of weight dependence, it requires hard b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(120 citation statements)
references
References 42 publications
4
114
1
1
Order By: Relevance
“…The average interevent interval was ϳ1.25 Hz, which approximately coincides with the intervals of spontaneous sharp waves measured in area CA3 in vitro (ϳ1.1-1.6 Hz) (Ellender et al, 2010;Hájos et al, 2013) and in vivo (0.01-2.0 Hz) (Buzsáki, 1986). The SWR events in CA1, which reflect the population synchrony in CA3, occur at average frequencies of 0.3-1.0 Hz during sleep (Eschenko et al, 2008;Girardeau et al, 2014). These values were also consistent with the prediction of our model.…”
Section: Temporal and Spatial Distributions Of Population Dynamicssupporting
confidence: 88%
See 1 more Smart Citation
“…The average interevent interval was ϳ1.25 Hz, which approximately coincides with the intervals of spontaneous sharp waves measured in area CA3 in vitro (ϳ1.1-1.6 Hz) (Ellender et al, 2010;Hájos et al, 2013) and in vivo (0.01-2.0 Hz) (Buzsáki, 1986). The SWR events in CA1, which reflect the population synchrony in CA3, occur at average frequencies of 0.3-1.0 Hz during sleep (Eschenko et al, 2008;Girardeau et al, 2014). These values were also consistent with the prediction of our model.…”
Section: Temporal and Spatial Distributions Of Population Dynamicssupporting
confidence: 88%
“…We show that the low-frequency spontaneous activity in our network model well replicates the lognormal features of hippocampal activity. Moreover, the bursting activity exhibited by our model resembles the complex spike bursts of hippocampal pyramidal neurons (Harris et al, 2001) observed frequently, but not always, during sharp-wave ripples (SWRs) (Buzsáki et al, 2002;Lee and Wilson, 2002;Foster and Wilson, 2006), which are transient oscillatory activities in CA1 and play a crucial role in memory consolidation (Girardeau et al, 2009;Ego-Stengel and Wilson, 2010;Carr et al, 2011). The SWRs originate from the activation of CA3 neural ensembles and typically occur when sensory influences on the hippocampus decrease during slow-wave sleep and immobility.…”
Section: Introductionmentioning
confidence: 64%
“…The eSTDP update includes log-STDP weight dependence, which produces a long-tailed distribution of weights (Gilson and Fukai, 2011). For every pair of a pre- and a postsynaptic spikes, the weight w e is modified by a quantity that depends on the current value of w e and the spike-time difference Δ t = t pre − t post :…”
Section: Resultsmentioning
confidence: 99%
“…These include weight dependence, so that weaker synapses potentiate more while stronger synapses express less potentiation, and in the limit even depress (Bi and Poo, 1998;van Rossum et al, 2000;Hardingham et al, 2007), and/or precise balancing of STDP rules for potentiation and depression (Abbott and Nelson, 2000;van Rossum et al, 2000;Kempter et al, 2001;Gütig et al, 2003;Morrison et al, 2007;Babadi and Abbott, 2010;Delgado et al, 2010;Gilson and Fukai, 2011). It was rigorously shown that STDP can lead to stabilization of the mean firing rate of the postsynaptic neuron if the integral of the learning window is negative (Kempter et al, 2001).…”
Section: Possible Mechanisms Preventing Runaway Synaptic Dynamicsmentioning
confidence: 99%